Optimizing Nitrogen Fertilizer for Maximizing Potato Yield and Profits in Farmer’s Field at Kaski District - Timilsina, Sandip; Khanal, Asmita; Timilsina, Chandra Kant; Upadhyay, Kalika Prasad (Journal of Nepal Agricultural Research Council, 2024)
An experiment was conducted during 2020 and 2021 in farmer’s fields at Machhapuchhre-06, Kaski, Nepal to determine the optimal amount of nitrogen for increasing potato yield, nutrient use efficiency (NUE) and net profits. Seven different levels of nitrogen (0, 25, 50, 75, 100, 125, and 150 kg/ha) were evaluated in a randomized complete block design with three replications. The effects of different levels of nitrogen on yield, yield-attributing traits, NUE, and production cost in potato cv. Janakdev were observed and recorded. It was found that applying nitrogen at the rate of 75 kg/ha, combined with 20 t farm yard manure (FYM)/ha produced the highest tuber yield and benefit-cost ratio. Application of nitrogen more than 75 kg/ha did not result any significant increase in yield and yield components. Considering agronomic, economic, and NUE factors, nitrogen application at 75 kg/ha along with 20 t/ha FYM was found to be optimal for the potato cultivation in Machhapuchhre, Kaski. This finding is also recommended for similar soil and agro-ecological conditions of Nepal.